Adaptation of the SIAF framework and related tools for the analysis of current mixed farming systems and MFS partner interventions in Malawi - Chikowo, Regis; Tufa, Adane; Chiduwa, Mazvita; Manda, Julius (International Institute of Tropical Agriculture, 2024)
In the coming decades, resource constraints over water, soil quality, biodiversity, livestock feed, and feed quality will increasingly negatively affect agricultural systems. Sustainable agroecosystems are those that tend to have a positive impact on natural, social and human capital. Sustainable intensification (SI) is defined as a system where agricultural performance is increased without adverse environmental impact and without the conversion of additional nonagricultural land into production. In much of Africa, any currently non-agricultural lands are likely to be marginal (Van Ittersum Martin, 2016), implying that their conversion to cropped lands would be associated with severe land degradation and unsustainable trade-offs. Unfortunately, for mixed farming systems, the synergies and trade-offs have not been adequately documented.